Role of sympathetic nervous system and neuropeptides in obesity hypertension - Hall,J.E. (2000)
Obesity is the most common cause of human essential hypertension in most industrialized countries. Although the precise mechanisms of obesity hypertension are not fully understood, considerable evidence suggests that excess renal sodium reabsorption and a hypertensive shift of pressure natriuresis play a major role. Sympathetic activation appears to mediate at least part of the obesity-induced sodium retention and hypertension since adrenergic blockade or renal denervation markedly attenuates these changes. Recent observations suggest that leptin and its multiple interactions with neuropeptides in the hypothalamus may link excess weight gain with increased sympathetic activity. Leptin is produced mainly in adipocytes and is believed to regulate energy balance by acting on the hypothalamus to reduce food intake and to increase energy expenditure via sympathetic activation. Short-term administration of leptin into the cerebral ventricles increases renal sympathetic activity, and long-term leptin infusion at rates that mimic plasma concentrations found in obesity raises arterial pressure and heart rate via adrenergic activation in non-obese rodents. Transgenic mice overexpressing leptin also develop hypertension. Acute studies suggest that the renal sympathetic effects of leptin may depend on interactions with other neurochemical pathways in the hypothalamus, including the melanocortin-4 receptor (MC4-R). However, the role of this pathway in mediating the long-term effects of leptin on blood pressure is unclear. Also, it is uncertain whether there is resistance to the chronic renal sympathetic and blood pressure effects of leptin in obese subjects. In addition, leptin also has other cardiovascular and renal actions, such as stimulation of nitric oxide formation and improvement of insulin sensitivity, which may tend to reduce blood pressure in some conditions. Although the role of these mechanisms in human obesity has not been elucidated, this remains a fruitful area for further investigation, especially in view of the current "epidemic" of obesity in most industrialized countries.